PERLINDUNGAN HUKUM DARI RAZIA KAMAR HOTEL/PENGINAPAN DI KOTA PALANGKA RAYA - Putri Fransiska Purnama Pratiwi (Fakultas Hukum Universitas PGRI Palangkaraya, 2019)
Legal Basis for Raids/Searching of Hotels/Inns by the Civil Service Police Unit (Satpol PP) in Palangka Raya is Government Regulation No. 16 of 2018 regarding the Civil Service Police Unit, matters relating to public order become the task of the Satpol PP. Satpol PP conducts raids if there are community reports, where the boarding house, the inn, is misused its function. In implementing the duty, the principle of presumption of innocence is still used. Reports will be responded to and when it is time to conduct a raid. Raids were also held not to find fault, but based on complaints from the community, whether there is really a deviation in the place. One legal effort that can be conducted by hotel/inn owners to provide legal protection for their guests is by not accepting spouses who are not husband and wife. Even if there are indeed different types of couples who want to stay offer to book two rooms, hence it does not cause negative perceptions from the Satpol PP who may conduct raids. Other legal remedies that can be done are to coordinate with the guest in order to submit a complete and clear identity and to include a letter of assignment when staying overnight in order to conduct duties so that the purpose of his arrival can be clearly identified to anticipate the occurrence of non-criminal acts committed in the room hotel/inn.